Manajemen Risiko dalam Prinsip Pembiayaan Mudarabah: Kajian Kontekstual Islam terhadap Risiko - Yudiana, Fetria Eka (IAIN Salatiga, 2010)
Risk management is one tool that can be used by companies to minimize the level of losses that are likely to occur or experienced by the company. Mudarabah is one form of cooperation in the field of finance which is based on the belief that financial trusts and investment trusts, moral hazard is one factor the risk faced by banking when they are confronted with a customer in the contract. The asymmetry of information provides opportunities for moral hazard and the occurrence of defaults that have a direct impact thelikelihood of losses for the company.